Cultural Worldviews and Environmental Risk Perception: A Cross-Cultural Study Using European Values Survey - Nawaz, Nafia (2020)
Climate change has become one of the most controversial topics of the twentieth century with the frequency and intensity of such events rising yearly. Unfortunately, the rise in the physical evidence has further intensified the existing divide on the topic of environmental risk. This deepening rift on the issue, which demands collective concrete actions, is affecting the feasibility and acceptance of climate change mitigation policies and measures. This research employed Kahan’s cultural cognitive theory (2008) to study the role of cultural orientation in polarization of European countries’ environmental risk perceptions. For this purpose, the European Values Survey Wave five, individual-level dataset was used to generate national level indexes for 33 European states. These indices were then employed to test the relationship between countries’ cultural worldviews, Inglehart’s post-materialistic values (1977) and environmental risk perception using scatterplots, correlation matrices and ordinary least square (OLS) regression analysis. The results proved that difference between grid and group dimension across countries was greater than within. The Western and Eastern Europe differing in their worldviews with Western states exhibiting higher egalitarian-communitarian attitudes. Additionally, the regression analysis found hierarchical-egalitarian index and post-materialistic index as significant while individualistic-communitarian index, age, average monthly income level (PPP in Euros) and education level as insignificant indicators of environmental concern. It was observed that countries with geographical, economic, social and historical closeness exhibited similar worldviews and therefore environmental attitudes.